Attenuation of nuclear orientation of In-127 in Gd and the InGd Korringa spin-lattice relaxation time constant - Stone, N; Ohya, S; Rikovska, J; Woehr, A; Betts, P; Dupak, J; Fogelberg, B; Jacobsson, L (2001)
The nuclear spin-lattice relaxation of In-127 implanted into pure gadolinium metal has been measured using the method of integral attenuation of on-line nuclear orientation. The Korringa constant is determined to be C-K ((InGd)-In-127, B-pol = 0.5 T) = 0.133(18) sK. The result is compared with relaxation of In nuclei in Fe.